SITOTOXICITY OF COMPOUND ISOLATED FROM THE LEAVES OF TITHONIA DIVERSIFOLIA (HEMSLEY) A.GRAY) AGAINST T47D, MCF-7 AND EVSA-T CELLS - Arfian Bela Mahardika; Subagus Wahyuono; Mae Sri Hartanti Wahyuningsih (Faculty of Pharmacy, Universitas Gadjah Mada, 2016)
Tithonia diversifolia (Hemsley) A. Gray) is one of the plants that are traditionally used to treat various diseases. The previous studies using Bioassay Guided Isolation methods has obtained the active compound (MTT, HeLa cells; IC50 9.776 g / mL). The cytotoxic effects of active compounds against breast cancer cells is unknown. This study aims to determine the cytotoxicity of theactive compound isolated from the leaves of T. diversifolia on breast cancer cells (T47D; MCF-7 and EVSA-T). The isolated compounds from T. diversifolia tested their cytotoxicity against breast cancer cells (T47D, MCF-7 and EVSA-T), using MTT method with a series of concentration of 0.39 to 50 ug/mL. Each concentration of the group performed triplicate and calculated the percentage of cell growth inhibition with probit analysis to calculate the IC50 value. The test results showed that the active compound have a cytotoxic effect on T47D, MCF-7 and EVSA-T cells with IC50 values are respectively (2.44; 4.697; 3.522) ug/mL, so this compound potential to be developed as an anticancer agent, especially breastcancer